1. ## Factor By Grouping

Factor By grouping.

a^2 x + bx - a^2 z - bz

a^2 x + bx = x (a^2 + b)

- a^2 z - bz = -z (a^2 + b)

My answer is (x - z)(a^2 + b).

Is this correct?

2. ## Re: Factor By Grouping

Yes that is correct, you can check your self too, just multiply out the bracketed terms!

3. ## Re: Factor By Grouping

Good to know that I did not mess this one up.

4. ## Re: Factor By Grouping

a^2 x + bx - a^2 z - bz

My answer is (x - z)(a^2 + b).
A quick way to "see" if correct is assign "easy to work with"
values to the variables; like with your problem:
a=1, b=2, x=3, z=4.
Substitute in both the original and the answer:
if both same, then "SUCCESS!".

5. ## Re: Factor By Grouping

Originally Posted by DenisB
A quick way to "see" if correct is assign "easy to work with"
values to the variables; like with your problem:
a=1, b=2, x=3, z=4.
Substitute in both the original and the answer:
if both same, then "SUCCESS!".
I am sure he will love this trick.

6. ## Re: Factor By Grouping

Originally Posted by DenisB
A quick way to "see" if correct is assign "easy to work with"
values to the variables; like with your problem:
a=1, b=2, x=3, z=4.
Substitute in both the original and the answer:
if both same, then "SUCCESS!".
Thank you very much.